2011
DOI: 10.1097/aln.0b013e3182289988
|View full text |Cite
|
Sign up to set email alerts
|

Sevoflurane Reduces Leukocyte and Platelet Adhesion after Ischemia-Reperfusion by Protecting the Endothelial Glycocalyx

Abstract: Sevoflurane reduces glycocalyx shedding in the postischemic coronary bed, maintaining the natural cover for endothelial adhesion molecules and, thus, reducing cell adhesion. This may explain beneficial outcomes linked to clinical use of volatile anesthetics after ischemia-reperfusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
97
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 132 publications
(104 citation statements)
references
References 53 publications
3
97
0
4
Order By: Relevance
“…26 The endothelial glycocalyx is a functional barrier and plays a critical role in maintaining the physiologically normal vascular permeability, and it can also prevent the adhesion of white blood cells and platelets to the walls of blood vessels. 7,16,27 Hence, the present study suggested that sevoflurane is likely to be therapeutically effective in reducing the liver tissue edema and inflammation induced by the ischemia-reperfusion injury. 17 Figure 1.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…26 The endothelial glycocalyx is a functional barrier and plays a critical role in maintaining the physiologically normal vascular permeability, and it can also prevent the adhesion of white blood cells and platelets to the walls of blood vessels. 7,16,27 Hence, the present study suggested that sevoflurane is likely to be therapeutically effective in reducing the liver tissue edema and inflammation induced by the ischemia-reperfusion injury. 17 Figure 1.…”
Section: Discussionmentioning
confidence: 98%
“…The time-dependent protective effects of sevoflurane on the shedding of HS and Syn-1 are likely dependent on the physiological association between these molecules and the endothelial glycocalyx, as well as the concentration of sevoflurane in the tissue.12,13 While HS is located on the surface of the endothelial glycocalyx and has a relatively loose association with the endothelial glycocalyx, Syn-1 is a core component of the endothelial glycocalyx and is located in its deeper layers. 3,8,10,16,[27][28][29] Therefore, when the endothelial glycocalyx is damaged, the peak of the HS release appeared earlier than that of Syn-1 (Figure 1a). Relatively loose association of HS with the endothelial glycocalyx likely contributes to the limited protective effect of sevoflurane on the shedding of HS at the beginning of the reperfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this structure is quite vulnerable and tends to disintegrate after application of various stressors, such as endotoxins, ischemia/hypoxia/ reperfusion, oxidative stress, among others. Damage to and modification of the EG are observed in many diseases including diabetes, ischemia, chronic infectious diseases, atherosclerosis, and tumors (van den Berg et al, 2003;Reitsma et al, 2007;Weinbaum et al, 2007;Becker et al, 2010b;VanTeeffelen et al, 2010;Chappell et al, 2011). The disintegration of EG predisposes to tissue infiltration by polymorphonuclears, monocyte/macrophages, and lymphocytes.…”
Section: Introductionmentioning
confidence: 99%